Teaching spelling : exploring commonsense strategies and best practices - Westwood, Peter (London : Routledge, 2014)
Teaching Spelling: Exploring Best Practices provides the vital knowledge and skills needed to help their students become proficient writers and spellers. Peter Westwood provides readers with a very clear and concise account of the important skills and processes that underpin accurate spelling, and describes in very practical terms, many evidence-based strategies and methods that teachers can use to help all students become confident, capable and independent spellers. The book also addresses the purposes of various forms of assessment of spelling skills, to guide teaching and planning. Chapters in this accessible, and timely text include: the importance of correct spelling visual, auditory and cognitive components of spelling ability general principles for planning instruction proven teaching strategies and methods word study as a teaching approach formal and informal assessment At the end of each chapter the author provides a list of online and print resources, thus enabling readers to extend their knowledge in the various topics. The extensive main reference list is also an invaluable source of information on recent research and thinking on the topic of spelling instruction. Teaching Spelling: Exploring Best Practices is an essential resource for all those in teacher education and taking in-service courses.
Includes bibliographical references and index.
Keywords: English language -- Orthography and spelling -- Study and teaching; EDUCATION / General